2022
DOI: 10.19044/esj.2022.v18n20p99
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Assessment of Shoreline Changes and Management of the Transgressive Mud Coast, Nigeria

Abstract: This study investigated changes due to erosion and the consequences of rising sea levels on the Transgressive mud coast of Nigeria using multispectral Landsat images and ALOS PALSAR (AW3D30) elevation models with the view of proffering a management strategy for a sustainable coast. Endpoint Rate (EPR) and Linear Regression Rate (LRR) techniques within the Digital Shoreline Analysis System (DSAS) were used to assess the rates of changes along the shoreline between 1986 and 2021. Inundation models were developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Sources of pollution from chemicals, particles, domestic wastes, industrial wastes, agricultural wastes, and noise, or the spread of invasive organisms affect the ocean in the Gulf of Guinea, resulting in habitat degradation, loss of biodiversity, and degeneration in human health (Akita et al, 2020). These led to various forms of environmental debacle such as flooding, coastal erosion, pollution of various degrees and types, chronic illnesses, loss of species, and the inability of the ocean to perform its natural function (Popoola, 2012(Popoola, , 2022. Coastal and ocean degradation is caused by impacts of climate change with grave consequences such as fishery depletion, rising sea levels, and threat to the survival of ecosystem biomes which serve as habitats for ecosystem wildlife (Popoola et al, 2019;Popoola, 2021).…”
Section: Challenges To the Development Of Be Frameworkmentioning
confidence: 99%
“…Sources of pollution from chemicals, particles, domestic wastes, industrial wastes, agricultural wastes, and noise, or the spread of invasive organisms affect the ocean in the Gulf of Guinea, resulting in habitat degradation, loss of biodiversity, and degeneration in human health (Akita et al, 2020). These led to various forms of environmental debacle such as flooding, coastal erosion, pollution of various degrees and types, chronic illnesses, loss of species, and the inability of the ocean to perform its natural function (Popoola, 2012(Popoola, , 2022. Coastal and ocean degradation is caused by impacts of climate change with grave consequences such as fishery depletion, rising sea levels, and threat to the survival of ecosystem biomes which serve as habitats for ecosystem wildlife (Popoola et al, 2019;Popoola, 2021).…”
Section: Challenges To the Development Of Be Frameworkmentioning
confidence: 99%
“…Shoreline changes have been studied using a variety of methods at local, regional and global scales with variant levels of accuracy. Some studies have utilized, remotely sensed satellite data (Bartsch et al, 2020;Popoola, 2022), historical maps (Pepe et al, 2023) as well as aerial photographs, LiDAR imagery and terrestrial/in-situ data. Recent advancements in the use of remote sensing techniques to monitor shoreline changes have shown promise in comparison to the traditional ground surveying method, which has proven to be relatively high in terms of cost, labour, and schedule (Klemas, 2013).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…By combining the high-resolution imagery obtained from the satellite and the great capability of the Geographic Information System (GIS) for data capturing, manipulation, processing and interpretation, the future position of the Lagoon Barrier coastline can be estimated creating an avenue for putting up measures that would manage the accompanying effects of this projection. In previous research, GIS technology has shown its promising strength in the handling of geospatial data like remotely sensed imagery to precisely, investigate shoreline changes (Oyinloye et al, 2016;Adefisan et al, 2018;Akinluyi et al, 2018;Fashea et al, 2022;Popoola, 2022;Pepe et al, 2023), however, no literature has used Sentinel-1 SAR imagery to forecast the future position of the Lagoon Barrier coastline in Lagos State. As an alternative to the previously used methodologies (Oyinloye et al, 2016;Adefisan et al, 2018;Akinluyi et al, 2018;Fashea et al, 2022;Popoola, 2022), this study presents an approach that uses extracted shorelines from Sentinel-1 Synthetic Aperture Radar (SAR) imagery to forecast the future position of the Lagoon Barrier Coast in Lagos State, Nigeria.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daramola et al [42] conducted a study on changes in coastal positions employing the linear regression rate (LRR), endpoint rate (EPR), and root mean square error (RMSE) methods. On the other hand, Popoola [43] employed the linear regression rate (LRR), endpoint rate (EPR), and ALOS PALSAR (AW3D30) elevation models to investigate shoreline changes.…”
Section: Introductionmentioning
confidence: 99%